2005
DOI: 10.1136/ard.2004.022053
|View full text |Cite
|
Sign up to set email alerts
|

Silica exposure is associated with increased risk of developing rheumatoid arthritis: results from the Swedish EIRA study

Abstract: Objective: To study the association between silica exposure and rheumatoid arthritis and how it is modified by cigarette smoking. Methods: Data were analysed from 276 male cases and 276 male controls aged 18 to 70 years, included in a Swedish population based study between May 1996 and June 2001. A case was defined as a person recently diagnosed with rheumatoid arthritis according to the ACR criteria. Controls were selected from the study base as a stratified random sample accounting for age, sex, and residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
125
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(132 citation statements)
references
References 33 publications
(31 reference statements)
1
125
1
5
Order By: Relevance
“…In contrast, another study reported crystalline silica exposure as an important risk factor for rheumatoid arthritis (21).…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, another study reported crystalline silica exposure as an important risk factor for rheumatoid arthritis (21).…”
Section: Discussionmentioning
confidence: 93%
“…10,11 In Scandinavia in particular, population-based case referent studies and linkage of census-defined occupation and hospitalization records have provided valuable insights into the potential relationships among occupational exposures, including to silica containing and other mineral dusts, and selected rheumatologic conditions, especially rheumatoid arthritis. [12][13][14][15][16][17][18][19] Sample size considerations, however, generally preclude occupationally-defined cohort investigations of rheumatologic diseases, especially conditions other than rheumatoid arthritis. A study of granite workers in Finland with more than 10,000 person years of observation that found a 70% increase risk of rheumatoid arthritis is a rare example of a cohort-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…Silica dust exposure, occurring in occupations such as rock drilling and mining, is a risk factor for ACPA positive RA, and an interaction can be seen between silica and smoking [98]. Hormonal factors are implicated by the fact that women are 2-4 times more likely to develop RA than men [99], and that RA usually develops at times when sex hormone levels change, i.e.…”
Section: Environmental Triggersmentioning
confidence: 99%